A New Perspective on Temperamental Shyness: Differential Susceptibility to Endoenvironmental Influences. Issue 3 (5th March 2013) - Schmidt, Louis A.; Miskovic, Vladimir
Abstract In this review, we adapt and extend a model recently used to account for differences in risk and resiliency outcomes to explain individual differences in temperamental shyness. The differential susceptibility to environmental influences model posits that heightened biological sensitivity and reactivity in the individual can predict different outcomes for better or for worse, depending on environmental influences outside (i.e., exogenous) of the individual. In this article, we extend this existing model and argue that the environment can also be conceptualized as a unique set of dynamic conditions and influences operating within (i.e., endogenous) the individual that are orthogonal to some biological sensitivity factors. In this new model, continuous brain electrical activity at rest constitutes one endogenous environmental condition that can vary (leftward to rightward) and influence gene expression to confer different outcomes, for better (sociability) or for worse (shyness). We then discuss how this model can be tested, as well as its potential implications for theory, development, and practice.